Identifying the electrocatalytic sites of nickel disulfide in alkaline hydrogen evolution reaction. (November 2017) - Ma, Qiuyu; Hu, Chengyi; Liu, Kunlong; Hung, Sung-Fu; Ou, Daohui; Chen, Hao Ming; Fu, Gang; Zheng, Nanfeng
Abstract: Transition-metal chalcogenides have attracted great attention for their superior catalytic activity towards hydrogen evolution reaction (HER) as an alternative to platinum. Here we report a facile method for synthesizing two-dimensional nickel disulfide (NiS2 ) by using Ni(OH)2 on nickel foam as substrate. The as-synthesized NiS2 displayed an activation period during HER with a remarkable structural and compositional change under alkaline conditions. Electrochemical in situ X-ray absorption spectroscopy revealed that metallic Ni acted as catalytic active species with superior activity of 67 mV to reach 10 mA cm −2 . The in situ generated metallic Ni were easily oxidized to large-area ultrathin Ni(OH)2 when exposed to air. The overall water splitting device was fabricated by using NiS2 -derived metallic Ni and Fe doped NiS2 -derived hydroxide as HER and OER electrode with a potential of 1.52 V to reach 10 mA cm −2 . Graphical abstract: Highlights: NiS2 nanosheets are transformed into ultrathin metallic Ni nanosheets under alkaline HER conditions. In situ X-ray absorption spectroscopy is applied to probe the change of electrocatalysts. Trace surface sulfide on Ni(0) promotes HER performance. An electrolyzer with a potential of 1.52 V to reach 10 mA cm −2 is built.